2020
DOI: 10.1002/adtp.201900183
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Graphene Quantum Dots, Iron, and Doxorubicin in/on Ferritin Nanocages for Bimodal Imaging and Drug Delivery

Abstract: Graphene quantum dots (GQDs) have been emerging as next‐generation bioimaging agents because of their intrinsic strong fluorescence, photostability, aqueous stability, biocompatibility, and facile synthesis. In this work, GQDs are encapsulated in ferritin protein nanocages to develop multi‐functional nanoplatforms toward multi‐modal imaging and cancer therapy. Encapsulation of ultra‐small GQDs is expected to reduce their quick excretion from the body and increase their bioimaging efficiency. To expand the func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 69 publications
(156 reference statements)
0
23
0
Order By: Relevance
“…By co-encapsulation of GQDs and iron inside the core of an engineered ferritin nanocage derived from the archaeon Archaeoglobus fulgidus , GQD-iron complexes in the ferritin nanocages were formed; the nanocages exhibited high relaxivity in MRI, and strong fluorescence at low pH values and on MDA-MB-231. Insignificant cytotoxicity and high DOX loading capacity of 35% suggested that his nanocarrier has the potential to be used as a pH-responsive fluorophore, MRI agent, and drug nanocarrier in cancer diagnosis and therapy [ 134 ]. DOX-loaded microspheres fabricated by reaction of GQDs and magnetic carbon modified with 3-aminopropyltrimethoxysilane using a maltose disaccharide molecule covalently attached to a third generation triazine dendrimer (Fe 3 O 4 @C@TDGQDs) were non-toxic on the A549 cells and showed pH-dependent DOX release; such microspheres can be considered as a new safe and efficient vehicle for the delivery of cancer drugs [ 135 ].…”
Section: Graphene Quantum Dotsmentioning
confidence: 99%
“…By co-encapsulation of GQDs and iron inside the core of an engineered ferritin nanocage derived from the archaeon Archaeoglobus fulgidus , GQD-iron complexes in the ferritin nanocages were formed; the nanocages exhibited high relaxivity in MRI, and strong fluorescence at low pH values and on MDA-MB-231. Insignificant cytotoxicity and high DOX loading capacity of 35% suggested that his nanocarrier has the potential to be used as a pH-responsive fluorophore, MRI agent, and drug nanocarrier in cancer diagnosis and therapy [ 134 ]. DOX-loaded microspheres fabricated by reaction of GQDs and magnetic carbon modified with 3-aminopropyltrimethoxysilane using a maltose disaccharide molecule covalently attached to a third generation triazine dendrimer (Fe 3 O 4 @C@TDGQDs) were non-toxic on the A549 cells and showed pH-dependent DOX release; such microspheres can be considered as a new safe and efficient vehicle for the delivery of cancer drugs [ 135 ].…”
Section: Graphene Quantum Dotsmentioning
confidence: 99%
“…The uptake of 131I-GQDs-PEG-FA at tumor sites can be clearly examined using SPECT images, which can attribute a more excellent permeability and retention effect and active targeting effect of AF to folate receptors. Also, Nasrollahi et al developed an image nanostructure based on ferritin protein (AfFtn-AA) nanocages that encapsulate the GQDs and iron (Fe) for fluorescence and magnetic resonance images [ 258 ]. It was then demonstrated that the non-target cells were underperforming.…”
Section: Reviewmentioning
confidence: 99%
“…The stability of some nanoparticles in aqueous physiological environments allows for successful loading and delivery of poorly water-soluble drugs [75]. Additionally, nanoparticles can be functionalized using different targeting or imaging agents in order to be utilized for imaging and targeted drug delivery applications [76]. Specifically, drug delivery using biocompatible nanocarriers has been introduced as an effective solution to overcome some challenges involved in oral drug administration, particularly for drugs with low stability, bioavailability, and solubility.…”
Section: Micro and Nanoscale Carrier Typesmentioning
confidence: 99%